براہوئی رسم الخط نا چارمرحلہ: The Four periods of Brahui Script - Abdul Raziq Ababaki; Sani, Dr.Liaquat Ali (Al-Burz, 2018)
This research paper discusses the four stages of Brahui script. Even though, the literary work in Brahuii language has been started since 1292 ? when “Khidmat e Deen’’ was published. But it is interesting to note here that instead of this huge historical gap, Brahui orthography has not been standardized. The influence powerful and regional languages have always influenced the writing style of Brahui Script. Till the end of Durkhani school of thought, influx of Arabic Alphabets brought the Arabic script for Brahui. Roman, Persian and new Roman was introduced for Brahui script in subsequent period. The main objective of this research paper is to show and identify the orthographical dilemma in Brahui and It further shows the analyses of deferent borrowing scripts and their phases. Two or three samples of each phase have been taken out for conducting this research. Finally, this paper ends with the result and conclusion that adoption of others scripts can create writing problem in future as well.